Meltwater Discharge From Marine‐Terminating Glaciers Drives Biogeochemical Conditions in a Greenlandic Fjord. Issue 11 (12th November 2022) - Kanna, Naoya; Sugiyama, Shin; Ando, Takuto; Wang, Yefan; Sakuragi, Yuta; Hazumi, Toya; Matsuno, Kohei; Yamaguchi, Atsushi; Nishioka, Jun; Yamashita, Youhei
Abstract: An increasing body of work has shown the potential impacts of subglacial discharge from marine‐terminating glaciers on the marine environment around Greenland. Upwelling of nutrients associated with rising buoyant plumes near the front of marine‐terminating glaciers plays a key role in maintaining the high productivity of connected fjords. The response of protist communities to subglacial discharges into fjords nevertheless remains poorly understood. Here we show data of water properties, nutrients, and protist communities during two summers in 2018 and 2019 in a Greenlandic fjord system fed by marine‐terminating glaciers. This study included the period of intense summer melting of the Greenland Ice Sheet in 2019. The data revealed high nutrient concentrations in 2019 that were attributed to intensified upwelling of nutrients and dissolved iron into the subsurface layer. The source of the iron and the nutrients was subglacial discharge and deep fjord water, respectively. Intense glacial discharges in 2019 mitigated nitrate and phosphate limitations of phytoplankton in the fjord and resulted in an increase of chlorophyll a in the subsurface layer and growth of large diatoms. Heterotrophic protists such as dinoflagellates, tintinnids, and nanoflagellates were more abundant in the summer of 2019. We concluded that nutrient upwelling by subglacial discharges was the major driver of the structure of lower trophic levels in fjord ecosystems. We hypothesize that the more intense melting of glaciers and related increase in subglacial discharge will enhance nutrient upwelling, and increased summer productivity in fjords until the glaciers retreat and terminate on land. Key Points: Higher nutrient concentrations in a Greenlandic fjord with marine‐terminating glaciers were found in 2019 compared to 2018 Intense summer melting during 2019 led to higher subglacial discharge and enhanced nutrient upwelling Intensified upwelling of nutrients into the euphotic zone increased productivity of large diatoms